2007
DOI: 10.22358/jafs/66724/2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variation in the proportion of solid- and liquid-associated rumen bacteria in duodenal contents on the estimation of duodenal bacterial nitrogen flow

Abstract: The aim of this research was to examine to what extent variation in the relative proportions of solid-(SAB) and liquid-associated rumen bacteria (LAB) in duodenal bacteria have an impact on the estimation of duodenal flow of bacterial N. For this, four dairy cows were fed diets varying in forage: concentrate ratio (80:20, 65:35, 50:50 and 35:65). SAB and LAB were separated from rumen contents four h after the morning feeding. Adenine, cytosine and odd and branched-chain fatty acids were determined both in SAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…This lack of relationship was surprising, because there was a substantial increase in microbial yield at the duodenum in response to increasing concentrates (Moorby et al, 2006). Nonetheless, there was a strong correlation between the flows of purine bases and of OBCFA in duodenal digesta in this study (Vlaeminck et al, 2006). This suggests that, in contrast to the results of Vlaeminck et al (2005), milk OBCFA are not useful microbial markers.…”
Section: Obcfacontrasting
confidence: 66%
See 2 more Smart Citations
“…This lack of relationship was surprising, because there was a substantial increase in microbial yield at the duodenum in response to increasing concentrates (Moorby et al, 2006). Nonetheless, there was a strong correlation between the flows of purine bases and of OBCFA in duodenal digesta in this study (Vlaeminck et al, 2006). This suggests that, in contrast to the results of Vlaeminck et al (2005), milk OBCFA are not useful microbial markers.…”
Section: Obcfacontrasting
confidence: 66%
“…A large number of studies over the last 40 yr have estimated microbial protein flow from the rumen using marker techniques and cannulated animals. Odd-and branched-chain fatty acids (OBCFA) are distinctive components of ru-men microorganisms (Harfoot, 1978) and have recently been used as markers of the microbial protein content within rumen and duodenal digesta (Vlaeminck et al, 2005(Vlaeminck et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings were limited to variations in dietary treatment. Vlaeminck et al [ 12 ] determined adenine, cytosine and odd and branched-chain fatty acids both in SAB and LAB and used them to estimate bacterial N flow in duodenal. The results suggested that, depending on the marker used, changes in the proportions of SAB and LAB can have a substantial impact on estimated duodenal flow of bacterial N. Vlaeminck et al [ 8 ] found that a large and independent dataset of OBCFAs could accuracy predict the molar proportions of volatile fatty acids in the rumen.…”
Section: Introductionmentioning
confidence: 99%